A Literature Review on Determinants of Individual Behavior in Philanthropic Organizations - Muhammad Choirur Roziqin; Atok Syihabuddin; Muhammad Auliyaaul Wafa; Farhan Muhammad Islam (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This article explores the factors that influence individual behavior within philanthropic organizations. In the context of organizations, individual behavior greatly determines operational success and the achievement of social goals. This research uses a literature study approach to analyze various relevant literatures, identifying internal and external factors that influence individual behavior. Internal factors include motivation, personality, and personal values, while external factors encompass social, cultural, and educational environmental conditions. Emphasis is placed on the importance of motivation as the primary driver of behavior, as well as how individual characteristics can influence dynamics within an organization. This article also discusses the role of philanthropic institutions in creating an environment that supports positive interactions and individual development. Thus, this research aims to provide insights for leaders of philanthropic organizations in designing effective strategies to enhance individual engagement and productivity, as well as contribute to the development of literature in the field of individual behavior in the context of philanthropy.